Active citizenship and participation through the media: a community project focused on pre-school and primary school children - Tomé, V.; Lopes, P.; Reis, B. C.; Dias, C. P. (Comunicação e Sociedade, 2019)
The project “Educação para a cidadania digital e participação democrática” [Digital citi-zenship education for democratic participation], which began in 2015, currently involves around 200 kindergarten and primary school children, their families, teachers and other members of the Caneças educational community, a neighbourhood in Odivelas, Lisbon. The project’s meth-odology is action research, its objective is to understand how a coordinated action by a school, families and the community, contributes to enabling three to nine-year-old children to become active digital citizens. This paper focuses on social participation activities of children through traditional and digital media and involves activities that include formal, non-formal and informal learning contexts. Results show that social participation of children through the media increased and gradually evolved from producing traditional media content (school newspaper) to produc-ing digital content (video). They also evidence that action research methodology, adjusted to context and deriving from prior understanding of the context, is an adequate methodology for developing this type of project. However, its adequate implementation implies the support of the school board, researchers’ support to the teachers and the involvement of journalists and/or other media professionals.